2021
DOI: 10.1016/j.ebiom.2021.103512
|View full text |Cite
|
Sign up to set email alerts
|

Neurochemical signs of astrocytic and neuronal injury in acute COVID-19 normalizes during long-term follow-up

Abstract: Background Neurologic manifestations are well-recognized features of coronavirus disease 2019 (COVID-19). However, the longitudinal association of biomarkers reflecting CNS impact and neurological symptoms is not known. We sought to determine whether plasma biomarkers of CNS injury were associated with neurologic sequelae after COVID-19. Methods Patients with confirmed acute COVID-19 were studied prospectively. Neurological symptoms were recorded during the acute phase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
125
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(148 citation statements)
references
References 33 publications
20
125
0
3
Order By: Relevance
“…Elevations in serum NF-L levels were reported inconsistently in studies plagued with small fibers, unadjusted for comorbidities, or limited to the most sick patients [ 12 , 32 , 35 , 94 , 119 , 120 , 121 ]. Gisslen et al reported the normalization of GFAP and NF-L six months after the resolution of COVID-19, but their patients continued to exhibit neurological symptoms and their study was limited to these markers [ 34 ]. Persistent elevations of several neurodegeneration markers suggest an ongoing pathological process in COVID survivors that is heterogeneous [ 38 , 43 , 44 , 46 , 51 , 52 , 55 , 87 , 94 , 111 , 122 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Elevations in serum NF-L levels were reported inconsistently in studies plagued with small fibers, unadjusted for comorbidities, or limited to the most sick patients [ 12 , 32 , 35 , 94 , 119 , 120 , 121 ]. Gisslen et al reported the normalization of GFAP and NF-L six months after the resolution of COVID-19, but their patients continued to exhibit neurological symptoms and their study was limited to these markers [ 34 ]. Persistent elevations of several neurodegeneration markers suggest an ongoing pathological process in COVID survivors that is heterogeneous [ 38 , 43 , 44 , 46 , 51 , 52 , 55 , 87 , 94 , 111 , 122 ].…”
Section: Discussionmentioning
confidence: 99%
“…These interactions can trigger the aggregation of the brain’s proteins when protective anti-folding mechanisms are impaired, potentially exacerbating ongoing neurodegeneration processes and effects of the non-specific inflammatory response [ 26 , 27 , 28 , 29 , 30 ]. Several case reports, case series, and research projects provided conflicting data regarding the levels of τ, Amyloid β1-42, and Amyloid β2-41 in COVID-19 [ 6 , 31 , 32 , 33 , 34 , 35 ]. In silica, analyses suggested molecular mimicry between the compromising of SARS-CoV-2 and nervous system proteins, but clinical correlations are not described [ 3 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher serum NfL concentrations were associated with worse clinical outcomes, such as mechanical ventilation and ICU admission, in hospitalized COVID-19 patients [ 79 ]. A longitudinal study showed that elevated NfL and GFAP concentrations normalized at 6-month follow-up, regardless of prior disease severity or persisting neurological symptoms, in all COVID-19 patients [ 80 ]. A longitudinal cohort study with time-series design to estimate the spectrum of biochemical dataset suggests two other biochemical markers, C-reactive protein (CRP) and urea nitrogen, are associated with the risk of COVID-19-related acute respiratory failure and death [ 81 ].…”
Section: Neuroimaging and Neurochemical Findings Of Brain Dysfunction In Covid-19 Patientsmentioning
confidence: 99%
“…Acute neurological signs include anosmia, ageusia, headache, altered mental status, seizures, and stroke (Iadecola et al, 2020;Balcom et al, 2021). Interestingly, headache, fatigue, dysgeusia, and anosmia are common in both mild and severe cases (Kanberg et al, 2021). However, it is yet to be established whether altered mental health is a result from an encephalopathy caused by a systemic inflammatory condition or an encephalitis caused by SARS-CoV-2 neuroinvasion (Iadecola et al, 2020;Balcom et al, 2021).…”
Section: Introductionmentioning
confidence: 99%